2021
DOI: 10.3389/fonc.2021.708040
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Invasive Meningioma Based on Brain-Tumor Interface Radiomics Features on Brain MR Images: A Multicenter Study

Abstract: BackgroundMeningioma invasion can be preoperatively recognized by radiomics features, which significantly contributes to treatment decision-making. Here, we aimed to evaluate the comparative performance of radiomics signatures derived from varying regions of interests (ROIs) in predicting BI and ascertaining the optimal width of the peritumoral regions needed for accurate analysis.MethodsFive hundred and five patients from Wuhan Union Hospital (internal cohort) and 214 cases from Taihe Hospital (external valid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 38 publications
(57 reference statements)
0
13
0
Order By: Relevance
“…As shown by the bar diagram, the Gray-Level Co-Occurrence Matrix (GLCM) is the most used one, followed by the Gray-Level Run Length Matrix (GLRLM) and the First Order. Interestingly, since 2021 deep learning features [93] were introduced, e.g., Hiremath et al [22] and Liu et al [94] .
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…As shown by the bar diagram, the Gray-Level Co-Occurrence Matrix (GLCM) is the most used one, followed by the Gray-Level Run Length Matrix (GLRLM) and the First Order. Interestingly, since 2021 deep learning features [93] were introduced, e.g., Hiremath et al [22] and Liu et al [94] .
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…believed that the tumor-brain interface was not correlated with brain invasion ( 14 ), while Joo et al. believed that the tumor-brain interface was important for the diagnosis of brain invasion ( 10 , 12 , 13 ). This study concluded that the tumor-brain interface was the most meaningful MRI feature, an independent risk factor for WHO grade and brain invasion, with the best diagnostic efficacy among all single variables ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Stress and severe illness can activate the hypothalamic-pituitary-adrenal (HPA) axis leading to elevations in cortisol that stimulate neutrophil demargination and maturation, as well as lymphocyte apoptosis [35][36][37][38][39]. Immunologically, severe illness increases the production of neutrophils from the bone marrow and can lead to lymphopenia via various proposed mechanisms [40][41][42]. Ultimately, a relative neutrophilia and lymphopenia can result, leading to an elevated NLR.…”
Section: Discussionmentioning
confidence: 99%